THE USE OF CALCULATION PROBLEMS IN THE TEACHING OF PHARMACEUTICAL CHEMISTRY - Galina Rizak (Borys Grinchenko Kyiv Metropolitan University, 2023)
The training of specialists in the field of pharmacy is an urgent issue for a developed, social and legal state. Ukraine is no exception, in the educational policy of which a special place is given to pharmaceuticals. The purpose of the work concerned the definition of qualitative methods of teaching pharmaceutical chemistry, in particular, based on the use of calculation problems during practical classes. The research used the methods of analysis, synthesis, comparison and generalization. The experimental and scientific base of the research is the Uzhhorod National University. The developed provisions were tested on students pursuing higher education in the specialty «Pharmacy, industrial pharmacy» of the Faculty of Medicine. It was revealed which of the tasks should be performed by students in the course of their individual activities, for example during independent work, as well as within classroom classes. Various approaches to the organization of the educational process, namely teaching of pharmaceutical chemistry, were characterized. In addition, the content of the above-mentioned academic discipline was considered and its priority for pharmacy students was determined. Also, the main types and directions of calculation problems related to pharmaceutical chemistry were characterized. So, the influence of this type of tasks on the level of knowledge and professional training of students, as well as the possibility of implementing the latter's acquired skills in practical activities, is revealed. The obtained conclusions can be effectively used both by teachers, during preparation for classes with students of higher pharmaceutical education studying pharmacy, and directly by students for independent development.